PENGEMBANGAN E-MODUL DENGAN MASALAH KONTEKSTUAL PADA MATERI PERBANDINGAN KELAS VII SMP - SUCI RAMADHANI BILQIS (Departemen Matematika, 2021)
This research aims to develop an e-module with contextual problems in ratio material for class VII SMP that meets valid and practical criteria. The type of research used is design research type development studies with the Plomp development model which consists of a preliminary analysis, the development stage. The research was conducted at SMPN 15 Padang with the research subjects being students of class VII.1 A and class VII.1 B. This research of data type is primary data, consisting of qualitative data and quantitative data. The data collection instruments were interview guidelines, validity instruments, and practicality instruments. The data obtained were then analyzed using quantitative and qualitative analysis techniques. The results showed that the e-module with contextual problems developed was valid and practical. Based on the validation and suggestions from the e-module validator with contextual problems, it fulfills the valid criteria is very valid. The results of the response of students in the one to one evaluation stage of practicality were very practical, while in the small group evaluation stage the practicality level was very practical. This shows that the e-module with contextual problems in the comparison material for class VII junior high school which was developed is valid and practical. Keywords — contextual problem , design research, e-module.